Development and Evaluation of Live Attenuated Staphylococcus aureus Vaccine for the Control of Mastitis in Dairy Lactating Buffaloes in Pakistan - Kashif, M; Nasir, A; Shakoor, A; Hussain, A; Waheed, U; SiKandar, A; Abbas, A (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was designed to assess the evaluation of live attenuated S. aureus vaccine (LSAV) in lactating dairy buffaloes. For this purpose, 100 lactating buffaloes one to two months after parturition, were divided into two equal groups i.e., B1 and B2. Two shots of LSAV were administered @ 5 ml subcutaneous (S/C) 30 days apart, while B2 was kept as unvaccinated control (UC) by using a placebo (Normal Saline) @ 5 ml S/C twice. All these were kept under observation for six months periods to check the various parameters. Monthly serum samples were used to measure the geometric mean antibody titers using modified indirect Haemagglutination test which were 4.3, 128, 291, 261, 261, 142, and 58 at 0, 30, 60, 90, 120, 150, and 180 days, respectively whereas it was 5.3, 4.0, 4.3, 4.9, 2.3, 3.0, and 4.6 on monthly intervals in UC group. Whey geometric mean antibody titer was higher in vaccinated treated animals as compared with the UC group during the whole study period. There was a very high somatic cell count in unvaccinated groups as compared with the vaccinated group. The results showed a significant increase of fat and protein during the study period in vaccinated group as compared with UC group. The prevalence of mastitis was lower in vaccinated group as compared with UC. It was concluded that LSAV has clinical efficacy in reduction of mastitis and somatic cell count and it should be an additional tool to prevent mastitis along with other control measures in dairy herds to maximize the profit.